Advanced Computing and Communication Technologies Proceedings of the 9th ICACCT, 2015 - Choudhary, Ramesh K.; Mandal, Jyotsna Kumar; Auluck, Nitin; Nagarajaram, H A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book highlights a collection of high-quality peer-reviewed research papers presented at the Ninth International Conference on Advanced Computing & Communication Technologies (ICACCT-2015) held at Asia Pacific Institute of Information Technology, Panipat, India during 27-29 November 2015. The book discusses a wide variety of industrial, engineering and scientific applications of the emerging techniques. Researchers from academia and industry present their original work and exchange ideas, information, techniques and applications in the field of Advanced Computing and Communication Technology.
Branch and Bound Algorithm for Vertex Bisection Minimization Problem -- A comparative Study of 7T, 8T, 9T and 10T SRAM with Conventional 6T SRAM Cell Using 180nm Technology -- A Survey of Hardware and Software Co-Design Issues for System on Chip Design -- Opportunistic Maximum-Likelihood Channel Assignment in Mesh Based Networks -- A Real-Time (on Premise) Baseline based DDoS Mitigation Scheme in a Hybrid Cloud -- Clustering Based Single-hop and Multi-hop Message Dissemination Evaluation under Varying Data Rate in Vehicular Ad-hoc Network -- PV-Based Distributed Generation Location Using Mixed Integer Non-Linear Programming in Deregulated Electricity Market -- Investigation of Deterministic and Random Cyclic Patterns in a Conventional Diesel Engine using Symbol Sequence Analysis -- Design of a Slotted Square Patch Antenna for 3G and 4G Wireless Communication.
Keywords: Computational intelligence; Artificial intelligence; Telecommunication; Computational Intelligence; Artificial Intelligence; Communications Engineering, Networks